On a multi-point discrete boundary value problem - Henderson, Johnny; Luca, Rodica (Journal of difference equations and applications, 2013)
We study the existence and non-existence of positive solutions for a system of nonlinear second-order difference equations subject to multi-point boundary conditions. The proof of the existence of positive solutions is based upon the Schauder fixed point theorem.